Kementerian Sumber Manusia (KSM), Putrajaya - Anuar, Haziq Izzudin; Mohd Azizon, Muhamad Aqil Fikri; Mod Khoir, Nurazim; Salman, Muhammad Iqmal Syauqi (2024)
Kementerian Sumber Manusia KSM) is an important machinery of the Government in the implementation and development of Government policies in relation to the welfare of workers and the interests of employers. KSM plays a critical role in maintaining and improving corporate harmony through the practice of tripartism for the progress of the country and the well-being of the people. KSM started as just a Department in 1904. It later developed into the Ministry of Labor and Social Welfare in 1962 and then changed to the Ministry of Labor and Industrial Relations in 1964. In 1971, it was named as the Ministry of Labor and People's Energy with four agencies in under them are the Department of Factories and Machinery, the Department of Labor and Industrial Relations, the Industrial Court and the Trade Union Registrar's Office. In 1984, it again changed its name to the Ministry of Labor and finally became the Ministry of Human Resources (KSM) in 1990. Over the decades, several new Departments were created to expand the scope of KSM's functions and responsibilities. The process of change and adaptation that KSM has gone through is in line with the rapid development and change that is happening in the country.